Material safety data sheets - Sanger, John M.; The MARCOM Group, Ltd. (Boothwyn, Pa. : The MARCOM Group, Ltd., 1993)
Deals with the handling of hazardous chemicals, and explains how to examine and identify a chemical. A material safety data sheet gives a description of chemicals on the job and explains how to condition your workplace to eliminate chemical exposure
Title from title screen
Executive producer, Donald L. Leonard
Keywords: Hazardous substances -- Safety measures; Laboratories -- Safety measures; Industrial safety